Broadcasting Finance in Transition / A Comparative Handbook - Blumler Jay G.; Nossiter T.J (Oxford University Press, 1991)
Policy Issues, Broadcasting Finance in Turmoil: An Introduction, The Economics of Broadcasting, Purity or Pragmatism: A Cross-Cultural Perspective on Public Service Broadcasting, The Organization and Financing of National Broadcasting Systems, Television in the United States: Funding Sources and Programming Consequences, British Television: A Mixed Economy, Broadcasting Structure and Finance: The Netherlands, Politics and Culture and Technology: The Holy Trinity of Canadian Broadcasting, Problems of Structure and Finance and Program Quality in the French Audio-Visual System, Broadcasting in Italy, Television in Sweden: Position and Prospects, Funding Down Under: The Australasian Experience, Approaches to Policy Solutions, The Electronic Dilemma of Television Adverising, Regulatory and Financial Issues in Transfrontier Television in Europe, Afterword: Recent Developments, Index.